New Five Year Plan (1978-83) Animal Husbandry and Diary Development Draft Annual Plan 1978-79 - Government of Andaman and Nicobar (Government of Andaman and Nicobar Islands, 1977)
The Draft Annual Plan 1978-79 for the Andaman and Nicobar Administration emphasizes strengthening Animal Husbandry and Dairy Development with a total outlay of Rs. 77.300 lakhs, distributed across 15 targeted schemes. Key initiatives include the establishment and upgradation of veterinary hospitals and dispensaries, disease control programs for Foot and Mouth Disease and Ranikhet Disease, and the development of a Cattle Breeding Farm at Port Blair to improve genetics and local cattle production. Poultry development is another focus area, aiming to expand existing farms and establish new units to reach 1800 layers and 4000 broilers by 1982-83. Training and skill development programs for farmers and departmental staff are incorporated to enhance technical capabilities in animal husbandry practices. The plan is expected to improve livestock health, increase productivity in milk, meat, and egg production, and generate employment opportunities for rural populations. By addressing animal health and enhancing breeding and production practices, the initiative aims to stimulate economic growth and support the livelihoods of marginal farmers, creating a sustainable framework for agricultural and rural development across the islands.
Andaman and Nicobar Administration, Sector - Animal Husbandry and Diary Development
Andaman and Nicobar Administration, Sector - Animal Husbandry and Diary Development
Keywords: Andaman And Nicobar Islands; Animal Husbandry; Dairy Development; Veterinary Services; Disease Control; Cattle Breeding; Poultry Development; Training Programs; Infrastructure Development; Economic Growth; Employment Generation; Livestock Productivity